2014
DOI: 10.2174/1871520614666140521122932
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Delivered Quercetin for Cancer Therapy

Abstract: Quercetin, a natural protective bioflavonoid, possesses diverse pharmacologic effects, such as antioxidant, anti-inflammatory, anti-proliferative, and anti-angiogenic activities. Recently, quercetin's effect in cancer prevention and treatment was recognized. However, the poor water solubility and low-bioavailability of quercetin limit its clinical use in cancer therapy. Nanotechnology provides a method to create novel formulations for hydrophobic drug. Nanoparticles-delivered quercetin has attracted many atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 63 publications
0
27
0
1
Order By: Relevance
“…When considering dietary sources, onions seem a good source as regards quantity and bioavailability [Lee and Mitchell, ]. In view of the low bioavailability arising from low aqueous solubility and intestinal absorption, one of the approaches that is being explored to improve flavonol bioavailabilty is delivery in a nanoparticle form [Men et al, ; Tran et al, ].…”
Section: Absorption and Bioavailabilitymentioning
confidence: 99%
“…When considering dietary sources, onions seem a good source as regards quantity and bioavailability [Lee and Mitchell, ]. In view of the low bioavailability arising from low aqueous solubility and intestinal absorption, one of the approaches that is being explored to improve flavonol bioavailabilty is delivery in a nanoparticle form [Men et al, ; Tran et al, ].…”
Section: Absorption and Bioavailabilitymentioning
confidence: 99%
“…NPs have also been used as drug delivery systems that enable unique approaches for tuberculosis treatment (Gelperina et al , ). In medical applications, the vast majority of studies have focused on fighting cancer using NPs (Alexis et al , ; Hallaj‐Nezhadi et al , ; Chatterjee et al , ; Miele et al , ; Men et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…25,29,30 Our results indicated that raw eupafolin may blend together with Eudragit E100 in the alcohol as hydrophobic phase, and then the hydrophilic end of PVA as an emulsion stabilizer can interpenetrate them during the nanoprecipitation process to finally form nanoparticles with reproducible size and uniform distribution; 2) The conversion of crystalline structure Figure 8 Eupafolin nanoparticle delivery system (ENDS) inhibited the activation of MAPKs in PM-stimulated HaCaT keratinocytes. Notes: (A-C) Effects of specific NADPH oxidase inhibitor apocynin (APO, 100 µM), antioxidant N-acetylcysteine (NAC, 100 µM), specific MAPK inhibitors (10 µM U0126, SB202190, and SP600125), ENDS (10 µM), and raw eupafolin (10 µM) on the phosphorylation status of (A) ERK, (B) p38, and (C) JNK in HaCaT keratinocytes stimulated with PM (50 µg cm −2 ) for 4 hours, as determined by Western blotting.…”
Section: Discussionmentioning
confidence: 82%
“…24 However, the chemical structure of flavonoids, such as quercetin and naringenin, has also limited their administration and application in clinical medicine, due to their extremely low water solubility and poor bioavailability. 25,26 Eupafolin has a similar flavone backbone structure and displays poor water solubility, resulting in poor cutaneous penetration following topical administration on skin. Therefore, many studies have attempted to develop nanoparticle delivery systems using nanoprecipitation and high pressure homogenization techniques to overcome the physicochemical drawbacks of the active compounds 27,28 and thereby improve their solubility and skin absorption.…”
Section: Introductionmentioning
confidence: 99%